2017
DOI: 10.3389/fpsyg.2017.00014
|View full text |Cite
|
Sign up to set email alerts
|

Mentalizing Makes Parenting Work: A Review about Parental Reflective Functioning and Clinical Interventions to Improve It

Abstract: In the last decade several studies have investigated the role of parental reflective functioning (RF), defined as the parental ability to understand his/her child’s mental states, on the child’s development. Herein, a narrative review on parental RF is presented aimed at (1) presenting an overview of the existing empirical studies, (2) pinpointing unrequited questions, and (3) identifying future research directions. Specifically, the current review focused on (a) the impact of parental RF on the quality of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
213
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(247 citation statements)
references
References 70 publications
7
213
1
7
Order By: Relevance
“…Past research has focused on how mentalization promotes sensitive behavior (e.g., Camoirano, ), leaving out the question of whether (and why) mentalization may not guide behavior under certain conditions. Deater‐Deckard () proposed that stress acts as an obstacle to parents' attempts to respond appropriately to their children's needs by promoting less under‐controlled, more reactive parenting.…”
Section: Maternal Mentalization and Behaviors During Observed Dyadic mentioning
confidence: 99%
“…Past research has focused on how mentalization promotes sensitive behavior (e.g., Camoirano, ), leaving out the question of whether (and why) mentalization may not guide behavior under certain conditions. Deater‐Deckard () proposed that stress acts as an obstacle to parents' attempts to respond appropriately to their children's needs by promoting less under‐controlled, more reactive parenting.…”
Section: Maternal Mentalization and Behaviors During Observed Dyadic mentioning
confidence: 99%
“…Studies have suggested that reflective parenting programs improve RF and parenting (Bammens, Adkins, & Badger, ; Pajulo et al., ; Sadler et al., ; Suchman, DeCoste, Castiglioni, et al., ; Suchman et al., ; Suchman, Ordway, de las Heras, & McMahon, ). Yet, it remains unclear whether changes in RF lead to the changes in parenting behavior or whether these changes happen simultaneously (see Camoirano, ; Sleed, Baradon, & Fonagy, ; Suchman et al., ). Therefore, it is important to measure both outcomes in intervention studies that aim to improve parenting.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the mental component of mind‐mindedness (mentalizing) may enable parents to respond to and interact with their infant in an attuned manner, both on a conscious and an unconscious level (e.g., by being sensitively responsive to infant cues, synchronous, cooperative, warm, and autonomy granting; Camoirano, 2017; Zeegers et al., 2017). The importance of parents’ “mind‐minded” stance on infants’ developing emotion regulation may become more evident in an example of the parent and infant interacting in a peekaboo game.…”
Section: Introductionmentioning
confidence: 99%